2004
DOI: 10.1111/j.1440-1827.2004.01682.x
|View full text |Cite
|
Sign up to set email alerts
|

GM‐CSF activates RhoA, integrin and MMP expression in human monocytic cells

Abstract: Monocyte migration is one of the key events occurring in the early stage of atherosclerosis. This process includes monocytic adhesion to and penetration through the arterial intima. In such an environment, many factors stimulate the monocytes to enhance integrin activation and extracellular matrix degradation. To investigate the coordinative operation of these two events in relation to monocyte migration, we paid particular attention to the effects of granulocyte-macrophage colony-stimulating factor (GM-CSF) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 50 publications
2
23
0
Order By: Relevance
“…In the present study an increased MMP-2 activity was detected in supernatants from B. abortus-infected osteoblasts. Previous studies have shown that in several cell lines MMP production can be stimulated by GM-CSF (25,26). Since this factor is produced by Brucella-infected osteoblasts, as shown here and also in our previous study (11), we assessed whether osteoblast-derived GM-CSF may induce MMP-2 in these same cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study an increased MMP-2 activity was detected in supernatants from B. abortus-infected osteoblasts. Previous studies have shown that in several cell lines MMP production can be stimulated by GM-CSF (25,26). Since this factor is produced by Brucella-infected osteoblasts, as shown here and also in our previous study (11), we assessed whether osteoblast-derived GM-CSF may induce MMP-2 in these same cells.…”
Section: Discussionmentioning
confidence: 99%
“…Proinflammatory cytokines and growth factors have been shown to stimulate MMPs secretion by different cellular types (20,25,26,43), in some instances in an autocrine fashion (2,21). To test whether MMP-2 induction in Brucella-infected osteoblasts may be mediated by cytokines or growth factors produced by these same cells, the levels of IL-1␤, IL-6, TNF-␣, and GM-CSF were measured in culture supernatants.…”
Section: Brucella Abortus Induces a Gm-csf-dependent Release Of Mmp-2mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, MMP-9 secretion was not stimulated by supernatants from noninfected FLS. Several cytokines and growth factors have been shown to stimulate MMP-9 production by monocytes, including IL-1␤, TNF-␣, and GM-CSF, and were candidates for mediators of the stimulating effect of synoviocyte culture supernatants (19,26,57). However, we have mentioned above that Brucella-infected FLS did not secrete IL-1␤ or TNF-␣.…”
Section: Vol 79 2011 Brucella-infected Synoviocytes Secrete Mmps 3621mentioning
confidence: 99%
“…Since GM-CSF and IL-6 are also known to induce MMP production by different cell types (8,26,46) and both factors are produced by Brucella-infected FLS ( Fig. 2A and B), we decided to test their potential role as mediators of the MMP-9 induction by culture supernatants from infected FLS.…”
Section: Vol 79 2011 Brucella-infected Synoviocytes Secrete Mmps 3621mentioning
confidence: 99%